MEMBANGUN PEMAHAMAN TENTANG SEJARAH DAULAH USMANI MELALUI METODE MIND MAPPING - Dewi Fitriyani; Ilham Hilmi Gymnastiar; Sindi Susana Putri; Haerudin; Rahma Dilla Zainuri (STKIP Subang, 2026)
This study aims to explore the effectiveness of the mind mapping method in improving students' understanding of the history of the Ottoman Empire. As a caliphate that played an important role in Islamic and world history, the material about the Ottoman Empire is often considered complicated and difficult to understand. The mind mapping approach was chosen because it has been proven to help organize information visually, increase engagement, and make it easier for students to remember historical facts. This study used a qualitative method with in-depth interview techniques and direct observation of grade IX students of SMPN 2 Telukjambe Timur who were learning about the Ottoman Empire. The results showed that the mind mapping method was able to improve students' understanding, make the learning process more interactive, and help students connect key concepts in the history of the Ottoman Empire. Thus, this study is expected to contribute to innovation in history learning in the classroom and enrich the literature related to Islamic history teaching strategies.